Implementation of problem based learning model with Newspaper media to improve students critical thinking In social science learning viii-a grade - Kanirawati, Kanirawati (International Journal Pedagogy of Social Studies, 2017)
This research was motivated by the low ability of student’s critical thinking in a group of Social Sciencelearning in VIII-A Grade SMP Pasundan 6 Bandung. The purpose of this research is to describe planning,implementation, result, obstacle and effort in the implementation of problem-based learning model withnewspaper media to improve student’s critical thinking ability. This research uses classroom actionresearch with Kemmis and Taggart model by using problem-based learning and newspaper as learningmedia. The subjects of this research are37 students of VIII-A Grade SMP Pasundan 6 Bandung. Planningof this research includes preparing RPP(Instruction Plan) and making instrument according to the needs.This research was conducted for three cycles and obtained the result of student’s critical thinkingimprovement in Social Science learning from first cycle until third cycle. The student’s critical thinkingability in the first with the enough category, in the second with the enough category and in the third cyclewith the good category. The increase is signed by the number of students who ask questions, answerquestions asked by teachers by using their own language and using sentences that are understandable, aswell ascan find and solve existing problems in the environment related to the subject in a group discussion activity. The problem of this research are the difficulty of finding newspapers related to thesubject presented and the implementation of lesson is inappropriate with the instruction plan. Theseobstacles can be solved by reading of newspapers from various sources before implementing the actionand improving the learning process by delivering the subject in accordance to the instruction plan that hasbeen compiled. This research uses qualitative and quantitative data analysis.